G199(P) An innovative approach to inter-professional paediatric simulation training: a facilitated 'hopes and concerns' conversation to enhance psychological safety. (25th October 2020) - Kilonback, A; Desai, B
Abstract : Background: Providing a safe and positive environment for learners within simulation is crucial, this need is often amplified with an inter-professional learner group on a mandatory course. Aims: Create a safe space to allow open and honest discourse to promote effective inter-professional learning through simulation. Methods: Staff from nursing and medical backgrounds were allocated time to attend the training day by their rota coordinators. Each training day commenced with a facilitated 'hopes and concerns' session. The participants wrote down their hopes and concerns regarding the simulation training day. These were collated by the facilitator who identified common themes and developed them through discussion with the group to promote psychological safety and formulate tailored learning objectives and ground rules. Participants completed pre and post course questionnaires and a focus group of faculty and learners was used to evaluate the effect. Results: The course was run on 16 separate days and was delivered to 137 learners representing a range of healthcare professionals including healthcare assistants, nurses, physician's associates and a variety of doctors from FY2 to consultants. All participants reported an improvement in their technical and non-technical skills and there were spontaneous recommendations from the participants that more paediatric training should be multi-professional. Allowing time to reflect on hopes and concerns and write them down enabled the facilitator to draw out comments from both the extroverts and introverts in the group. Common themes with regard to hopes included developing technical and non-technical skills. Common themes with regard to concerns were feeling stressed, nervous, embarrassed, being judged and intimidated. These themes were shared across professions and levels of seniority. Faculty members remarked that the new introduction 'improved engagement and participation in the debrief'. Learners commented that the introduction 'levelled the playing field' and in the debrief they felt 'safe to discuss their own feelings, previous experiences and mistakes'. Some additional comments from the post-course questionnaire included 'great team support', 'empowering day', 'extremely non-judgmental' and 'made to feel comfortable.' Conclusions: Inter-professional simulation training with a hopes and concerns facilitated discussion improves leaners engagement with simulation training leading to development of confidence and skills.